Linking Up to Development? Global Value Chains and the Making of a Post-Washington Consensus - Werner, Marion (2014)
Over the last decade, the global value chain (GVC) approach, with its associated notions of chain governance and firm upgrading, has proliferated as a mode of analysis and of intervention amongst development institutions. This article examines the adoption and adaptation of GVCs at four multilateral agencies in order to understand the purchase of value chain approaches within the development field. Mixing GVC perspectives with other theoretical influences and applied practices, these institutions deploy value chain frameworks to signal a new generation of policies that promise both to consolidate, and to advance beyond, the market fundamentalism of the Washington Consensus. To achieve this, value chain development frameworks craft interventions directed toward various constellations of firm and non-firm actors as a ‘third way’ between state-minimalist and state-coordinated approaches. The authors identify key adaptations of the GVC framework including an emphasis on value chain governance as an instrument to correct market failure in partnership with state and development agencies, and upgrading as a de facto tool for poverty reduction. They find that efforts are ongoing to construct a ‘post’ to the Washington Consensus and that the global value chain is enabling this process by providing a new language and new object of development intervention: ‘the chain’ and the local–global linkages that comprise it.